Landscape educational trail to the highest peak of Ukraine Mount Hoverla (Ukrainian Carpathian Mountains) - Melnyk, Anatolij; Lavruk, Maria (Journal of Education, Health and Sport, 2017)
The route of the landscape path to the highest peak of Ukraine, mount Hoverla, has been developed on the basis of comprehensive landscape research of the north-eastern sector of the Chornohora landscape and compiled landscape maps. The route is the landscape educational trail which demonstrates natural territorial complexes of various ranks, revealing the integrity of nature through the interaction of its components. The definition of the nature, purpose, tasks and character of the landscape educational trail is provided. The trail developed by the authors passes through six landscape high-altitude areas, which in turn consist of a series of landscape terrains. The route involves stops in each high-altitude area to clarify: 1) the name of the area; 2) the morphological structure of a high-altitude area (a set of typical natural territorial complexes of the lower rank - landscape terrains, tracts and facies which form its horizontal structure); 3) anthropogenic impact on natural systems; 4) physical and geographical phenomena and processes.